2017
DOI: 10.7575/aiac.ijkss.v.5n.3p.6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Positional Differences in Fitness of Male University Ice Hockey Players and the Frequency, Time Spent and Heart Rate of Movement Patterns during Competition

Abstract: Background:  Men’s university ice hockey has received little scientific attention over the past 30 years, a time in which the traits of the players and the demands of the game have evolved.  Objectives: This study compared the physiological characteristics of university ice hockey players and examined the frequency and duration of the different movement patterns and heart rate (HR) responses during competition. Methods: Twenty male ice hockey players from the same team ( age ± SD = 22±2 years) underwent a fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
12
0
1
Order By: Relevance
“…Subsequently, PO was increased by 40 W every 2 min by increasing the resistance setting but maintaining the pedal rpm until a systematic increase (breakpoint) in the ventilatory equivalent for VCO 2 was observed on the graphical display of the metabolic measurement system software (25, 26). PO was then increased by 40 W every minute until volitional exhaustion was reached (27). Respiratory gas exchange was measured using a Rudolph valve and head gear apparatus (Hans Rudolph Inc., Shawnee Mission, USA) and a metabolic measurement system (Medgraphics CPX™, St. Paul, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, PO was increased by 40 W every 2 min by increasing the resistance setting but maintaining the pedal rpm until a systematic increase (breakpoint) in the ventilatory equivalent for VCO 2 was observed on the graphical display of the metabolic measurement system software (25, 26). PO was then increased by 40 W every minute until volitional exhaustion was reached (27). Respiratory gas exchange was measured using a Rudolph valve and head gear apparatus (Hans Rudolph Inc., Shawnee Mission, USA) and a metabolic measurement system (Medgraphics CPX™, St. Paul, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The oxygen uptake associated with the breakpoints for the ventilatory equivalent of VO 2 (VT1) and VCO 2 (VT2) was determined from the graphical display of these relationships after agreement by two different investigators (25, 26). Peak oxygen consumption (VO 2 peak) was defined as the highest VO 2 reached prior to exhaustion (27). Heart rate (HR) was measured every minute using a Polar® T31 HR monitor (Polar Electro, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…In complement to off-ice functional performance tests, on-ice tests are useful as for determining the physiological demands of hockey. For example, attributes such as aerobic capacity [ 20 ], the ability to perform repeated sprints [ 21 , 22 ] and other ice hockey’s physiological demands [ 23 , 24 ] have been observed and defined by scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Bandy has also similarities to ice hockey regarding the skating movement pattern which includes high-intensity skating, direction changes, and rest periods such as gliding. It has been shown that a combination of dynamic skating movement, shooting, and passing are important qualities in ice hockey (Jackson et al, 2017) and it is reasonable to believe that same fundamental qualities are important in bandy. In ice hockey, it has been demonstrated that offensive position (forwards) has higher anaerobic capacity in relation to defensive players (Douglas et al, 2019).…”
mentioning
confidence: 99%
“…In ice hockey, it has been demonstrated that offensive position (forwards) has higher anaerobic capacity in relation to defensive players (Douglas et al, 2019). It has also been shown that offensive position (forwards) spends more time in high-intensity skating and glided for a longer time in relation to defensive players (Douglas et al, 2019;Jackson et al, 2017).…”
mentioning
confidence: 99%